2016
DOI: 10.1016/j.jphys.2016.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a guideline-based clinical pathway of care to improve health outcomes following whiplash injury (Whiplash ImPaCT): protocol of a randomised, controlled trial

Abstract: This research is significant as it will be the first study to address the heterogeneity of whiplash by implementing a clinical pathway of care that matches evidence-based interventions to projected risk of poor recovery. The results of this trial have the potential to change clinical practice for WAD, thereby maximising treatment effects, improving patient outcomes, reducing costs and maintaining the compulsory third party system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 0 publications
0
32
0
Order By: Relevance
“…However, studies in a workers’ compensation setting have shown that early screening and intervention in people with musculoskeletal injuries with high chances of poor recovery resulted in significant cost reduction [22, 23]. This approach has also been shown to result in improved outcomes and reduced cost in low back pain in the UK [24], and is now being investigated in Australia for the management of whiplash [25]. For an optimal treatment approval process, it is recommended that claims managers in the compensation system not only approve evidence based treatment, but also encourage the use of psychosocial assessment tools, that for example, predict chronic pain and disability, after which they should offer the earliest intervention available.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies in a workers’ compensation setting have shown that early screening and intervention in people with musculoskeletal injuries with high chances of poor recovery resulted in significant cost reduction [22, 23]. This approach has also been shown to result in improved outcomes and reduced cost in low back pain in the UK [24], and is now being investigated in Australia for the management of whiplash [25]. For an optimal treatment approval process, it is recommended that claims managers in the compensation system not only approve evidence based treatment, but also encourage the use of psychosocial assessment tools, that for example, predict chronic pain and disability, after which they should offer the earliest intervention available.…”
Section: Discussionmentioning
confidence: 99%
“…For the whiplash clinical prediction rule, it is proposed that patients identified at low-risk of poor recovery require minimal treatment consisting of advice, reassurance and simple exercises [70]. In contrast, it is suggested that patients identified at high risk of poor recovery will require further assessment of potentially contributory factors including psychological distress, nociceptive processing, and neck movement and strength [70]. Whether or not this risk stratified targeted approach results in better patient outcomes is currently being evaluated with no data yet available.…”
Section: Patient Stratification and Sub-groupingmentioning
confidence: 99%
“…This qualitative descriptive study was nested within a larger investigation that aimed to improve recovery from WAD through the development of targeted treatment pathways based on whiplash CPR categorisation. 11 Focus group discussions were considered optimal in exploring clinicians’ understanding and practice behaviours regarding CPRs as comparison of multiple participants’ perceptions enables the identification of group norms and values, provides insight into how and why individuals think and act as they do and renders rich experiential data. 23 24 …”
Section: Methodsmentioning
confidence: 99%
“… 9 10 Additionally, a randomised controlled trial (Whiplash ImPaCT) is being conducted to determine whether targeted treatment based on CPR stratification is superior to usual care. 11 While the whiplash CPR's predictive accuracy has been demonstrated in a validation study, 9 a trial such as Whiplash ImPaCT is needed to determine whether adoption of the CPR improves patient outcomes and/or the cost-effectiveness of care. This process is required before widespread CPR implementation is advocated.…”
Section: Introductionmentioning
confidence: 99%